Perbedaan Tingkat Insomnia Pada Wanita Pramenopaus Dan Menopause Di Perumahan Jetis Permai Gentan Baki Sukoharjo - Gunadarma, Raden Sakya Pradipta (2016)
Background.A person's ageis horizontally withsleep temporary disorder or permanent disorder incidence. Prevalence ofinsomniaincreases by age. Decreasing estrogen levelsin menopause womanisassociatedwith the incidence ofinsomnia. Chronicinsomniais foundin menopause womanandthis iscorrelatedwithsensationof heatwithsweating which influence woman's daily activity. Purpose. To determine and analyze the difference level of insomnia at premenopause and menopause woman of Regency Jetis Permai Gentan Baki Sukoharjo. Method. This study is an observational analytic research with cross sectional design with samples of 38 pramenopause woman and 38 menopause woman with a purposive sampling method. Test analysis used t-unpaired test. Method. This study is an observational analytic research with cross sectional design of the study population was. The selection of sample with a purposive sampling method obtained 38 pramenopause woman and 38 menopause woman who fit the inclusion criteria. Test analysis used t-unpaired test. Result. Insomnia level of premenopause woman is 5,58 meanwhile menopause woman is 7,66. p-value= 0,004 (p<0,05) so that statiscally, it means theres is a significan difference insomnia level of premenopause and menopause. Conclusion : This research concludes that insomnia level of menopause woman is more higher than premenopause woman of Regency Jetis Permai Gentan Baki Sukoharjo.